On the relationship between tibia torsional deformation and regional muscle contractions in habitual human exercises in vivo. Issue 3 (5th February 2015) - Yang, Peng-Fei; Kriechbaumer, Andreas; Albracht, Kirsten; Sanno, Maximilian; Ganse, Bergita; Koy, Timmo; Shang, Peng; Brüggemann, Gert-Peter; Müller, Lars Peter; Rittweger, Jörn
Abstract The mechanical relationship between bone and muscle has been long recognized. However, it still remains unclear how muscles exactly load on bone. In this study, utilizing an optical segment tracking technique, the in vivo tibia loading regimes in terms of tibia segment deformation in humans were investigated during walking, forefoot and rear foot stair ascent and running and isometric plantar flexion. Results suggested that the proximal tibia primarily bends to the posterior aspect and twists to the external aspect with respect to the distal tibia. During walking, peak posterior bending and peak torsion occurred in the first half (22%) and second half (76%) of the stance phase, respectively. During stair ascent, two noticeable peaks of torsion were found with forefoot strike (38% and 82% of stance phase), but only one peak of torsion was found with rear foot strike (78% of stance phase). The torsional deformation angle during both stair ascent and running was larger with forefoot strike than rear foot strike. During isometric plantar flexion, the tibia deformation regimes were characterized more by torsion (maximum 1.35°) than bending (maximum 0.52°). To conclude, bending and torsion predominated the tibia loading regimes during the investigated activities. Tibia torsional deformation is closely related to calf muscle contractions, which further confirm the notion of the muscle–bone mechanical link and shift the focus from loading magnitude to loading regimes in bone mechanobiology. It thus is speculated that torsion is another, yet under-rated factor, besides the compression and tension, to drive long bone mechano-adaptation.